Impact of accreditation on documentation and staff perception in the ophthalmology department of an Indian medical college - Ajay, K (Indian J Ophthalmol, 2021)
PURPOSE: National Accreditation Board for Hospitals and Healthcare Providers operates the health-care accreditation program in India. Research on impact of accreditation on eye-care centers is scarce. This article was conceptualized to scientifically evaluate the changes in documentation brought about by accreditation and its effects on staff in the Ophthalmology Department of an Indian Medical College. METHODS: This was conducted as a quasi-experimental study in four steps. First, a point-based evaluation of case sheets in both pre-accreditation and postaccreditation phase, along with statistical analysis of the results, was done. Step two involved analysis of quality indicators and patient safety indices in successive years from inception of data to post-accreditation phase. Step three comprised a survey of staff employing a validated tool, and finally, face-to-face semistructured interviews with designated authorities, including finance departmental head, completed the study. RESULTS: A statistically significant difference was seen in scores achieved by the pre and postaccreditation case sheets, with the postphase case sheets achieving 15% increased scores over the prephase case sheets. Quality indicator indices displayed improvements post-accreditation. There was an accompanying increase in quantity of documentation. Financial data analysis showed increased expenditure for accreditation under multiple heads. Staff believed that accreditation led to increased workload but did not express decreased satisfaction and felt that accreditation was eventually beneficial. However, staff believed rewards for improving quality can be enhanced. CONCLUSION: Accreditation increases quality and quantity of documentation, and staff workload. Increased financial costs also ensue.Staff believe that accreditation improves quality, is beneficial, but desire enhanced rewards.